Malignant Eyelid Tumors in India: A Study of 536 Asian Indian Patients - Kaliki, Swathi (Ocul Oncol Pathol, 2019)
PURPOSE: To study the proportion of eyelid malignant tumors in an Asian Indian population and to review their clinical features and outcomes. METHODS: This is a retrospective study of 536 patients. RESULTS: The mean age at presentation with eyelid malignancy was 58 years. Histopathology-proven diagnoses of these patients included sebaceous gland carcinoma (SGC) (n = 285, 53%), basal cell carcinoma (BCC) (n = 128, 24%), squamous cell carcinoma (SCC) (n = 99, 18%), and miscellaneous tumors (n = 24, 4%). The statistically significant differences between eyelid malignant tumors included age at presentation, tumor location, and tumor extent. The clinicopathological correlation of SGC, BCC, SCC, and miscellaneous tumors was 91, 86, 46, and 38% (p = 0.001), respectively. Comparing SGC with BCC, SCC, and miscellaneous tumors, SGC was more commonly associated with tumor recurrence (21 vs. 3, 8, and 13%; p = 0.001), systemic metastasis (13 vs. 0, 4, and 13%; p = 0.001), and death (9 vs. 0, 4, and 0%; p = 0.004). Compared to SGC, BCC, and SCC, locoregional lymph node metastasis was more common with miscellaneous tumors (26 vs. 16, < 1, and 8%; p = 0.001) over a mean follow-up period of 19 months. CONCLUSION: In Asian Indians, SGC is twice as common as BCC and 3 times more common than SCC. SGC is associated with poorer prognosis compared to other eyelid malignant tumors.